2006
DOI: 10.4269/ajtmh.2006.75.327
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Isolation of Highly Pathogenic H5n1 Avian Influenza a Viruses From Blow Flies Collected in the Vicinity of an Infected Poultry Farm in Kyoto, Japan, 2004

Abstract: During the outbreak of highly pathogenic avian influenza that occurred in Tamba Town, Kyoto Prefecture in 2004, a total of 926 flies were collected from six sites within a radius of 2.3 km from the poultry farm. The H5 influenza A virus genes were detected from the intestinal organs, crop, and gut of the two blow fly species, Calliphora nigribarbis and Aldrichina grahami, by reverse transcription-polymerase chain reaction for the matrix protein (M) and hemagglutinin (HA) genes. The HA gene encoding multiple ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 22 publications
1
65
0
3
Order By: Relevance
“…Sawabe et al (2006) suggested that blowflies carrying highly pathogenic avian influenza H5N1 were responsible for the outbreak of avian influenza in Japan in 2004. Nielsen et al (2011) reported that low pathogenic avian influenza H5N7 and H7N1 remained viable in the digestive tract of houseflies.…”
Section: 12mentioning
confidence: 99%
“…Sawabe et al (2006) suggested that blowflies carrying highly pathogenic avian influenza H5N1 were responsible for the outbreak of avian influenza in Japan in 2004. Nielsen et al (2011) reported that low pathogenic avian influenza H5N7 and H7N1 remained viable in the digestive tract of houseflies.…”
Section: 12mentioning
confidence: 99%
“…High-pathogenicity avian influenza H5N1 viruses have been detected in flies captured within a radius of 1.4 miles (2.25 km) around infected premises, 33 and wind can carry flies over long distances.…”
Section: Number Of Outdoor Flies On the Infected Premises (R 7 )mentioning
confidence: 99%
“…Research carried out during an HPAI outbreak in Kyoto, Japan in 2004, found that flies caught in proximity to broiler facilities where the outbreak took place, carried the same strains of H5N1 influenza virus as found in chickens of an infected poultry farm (Sawabe et al, 2006). A study in Denmark found that as many as 30,000 flies may enter a broiler facility during a single flock rotation in the summer months (Hald et al, 2004), suggesting that the impact of insect vectors may be significant.…”
Section: Biosecurity In Industrial Animal Systemsmentioning
confidence: 99%